Microglial inhibitory factor (MIF/TKP) mitigates secondary damage following spinal cord injury - Jaime Emmetsberger; Stella E. Tsirka (Neurobiology of Disease, 2012)
Spinal cord injury (SCI) induces an immune response during which microglia, the resident immunocompetent cells of the central nervous system, become activated and migrate to the site of damage. Depending on their state of activation, microglia secrete neurotoxic or neurotrophic factors that influence the surrounding environment and have a detrimental or restorative effect following SCI, including causing or protecting bystander damage to nearby undamaged tissue. Subsequent infiltration of macrophages contributes to the SCI outcome. We show here that suppressing microglia/macrophage activation using the tripeptide macrophage/microglia inhibitory factor (MIF/TKP) reduced secondary injury around the lesion epicenter in the murine dorsal hemisection model of SCI; it decreased the hypertrophic change of astrocytes and caused an increase in the number of axons present within the lesion epicenter. Moreover, timely inhibition of microglial/macrophage activation prevented demyelination and axonal dieback by modulating oligodendrocyte survival and oligodendrocyte precursor maturation. Microglia/macrophages located within or proximal to the lesion produced neurotoxic factors, such as tumor necrosis factor alpha (TNF-α). These results suggest that microglia/macrophages within the epicenter at early time points post injury are neurotoxic, contributing to demyelination and axonal degeneration and that MIF/TKP could be used in combination with other therapies to promote functional recovery.